2017
DOI: 10.1186/s12913-017-2151-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring public sector physicians’ resilience, reactions and coping strategies in times of economic crisis; findings from a survey in Portugal’s capital city area

Abstract: BackgroundEvidence is accumulating on the impact of the recent economic crisis on health and health systems across Europe. However, little is known about the effect this is having on physicians - a crucial resource for the delivery of healthcare services. This paper explores the adaptation to the crisis of public sector physicians and their ability to keep performing their functions, with the objective of gaining a better understanding of health workers’ resilience under deteriorating conditions.MethodsWe cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
16
0
4
Order By: Relevance
“…These subthemes have been explored in the literature previously as mechanisms by which physicians cope with the demands of the high-pressure, stressful profession [ 26 ]. One Portuguese study identified an association between work-life balance and a lack of resilience leading to the intention to leave work amongst public sector physicians [ 39 ]. However, it is clear that many physicians are unable to achieve such balance in their own lives due to conflicts with work and the duties required of them, reflecting how the ability to withstand stress is closely linked to context [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These subthemes have been explored in the literature previously as mechanisms by which physicians cope with the demands of the high-pressure, stressful profession [ 26 ]. One Portuguese study identified an association between work-life balance and a lack of resilience leading to the intention to leave work amongst public sector physicians [ 39 ]. However, it is clear that many physicians are unable to achieve such balance in their own lives due to conflicts with work and the duties required of them, reflecting how the ability to withstand stress is closely linked to context [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, another paper was excluded as despite its title, ("Exploring public sector physicians' resilience, reactions and coping strategies in times of economic crisis; findings from a survey in Portugal's capital city area"), it did not measure resilience but focused on working hours and intention to migrate in doctors. [18] This resulted in a final count of 24 eligible papers (Figure 1).…”
Section: Inclusion Criteria Exclusion Criteriamentioning
confidence: 99%
“…Adicionalmente, este trabalho apresenta apenas a análise descritiva dos dados recolhidos no estudo, cuja análise detalhada é apresentada em outras publicações. 20,28 No entanto, apesar destas limitações, realizou-se um retrato de um dos maiores hospitais do país e dois ACES que servem uma elevada população da área da Grande Lisboa.…”
Section: Discussionunclassified